A Retrospective Study of COVID-19 Vaccine Reactogenicity and Reinfection Susceptibility by ABO Blood Group in a Libyan Academic Community - A. Etwebi , Khawla; A. Gueder , Nahla; A. Etwebi , Raeefa; A. Alhamdani , Furdos (Libyan Journal of Medical and Applied Sciences, 2025)
Several reports have suggested that ABO blood groups and different COVID-19 vaccine platforms may influence susceptibility to infection and the pattern of post-vaccination reactions. In this study, we examined these factors in an academic community in Northwestern Libya. A total of 418 participants completed an online survey conducted between June and October 2022. Among them, 213 individuals (50.9%) reported previous COVID-19 infection, with the following blood group distribution among the infected: A (39%), O (38%), B (15.5%), and AB (7.5%). When blood group O was compared with all non-O groups combined (A, B and AB), individuals with group O showed a lower likelihood of reinfection (OR = 0.48, 95% CI: 0.24–0.96, p = 0.036). Additionally, most respondents (76.1%) had received at least one vaccine dose, and the pattern of reported side effects differed by vaccine type (p < 0.0001). Statistically, viral-vector vaccines (Sputnik V and AstraZeneca) were more frequently associated with systemic symptoms such as fatigue, headache, and fever. In contrast, recipients of the inactivated Sinopharm vaccine reported fewer reactions. These findings provide locally relevant information for the Libyan population and suggest that blood group O may be associated with a reduced risk of reinfection, and that the vaccine platform appears to influence short-term side-effect profiles experienced by the subjects.